WNT4 overexpression and secretion in thymic epithelial tumors drive an autocrine loop in tumor cells in vitro - Zhang, Xiaonan; Schalke, Berthold; Kvell, Krisztian; Kriegsmann, Katharina; Kriegsmann, Mark; Graeter, Thomas; Preissler, Gerhard; Ott, German; Kurz, Katrin; Bulut, Elena; Ströbel, Philipp; Marx, Alexander; et al. (Frontiers in Oncology, 2022)
Background: WNT4-driven non-canonical signaling is crucial for homeostasis and age-related involution of the thymus. Abnormal WNT signaling is important in many cancers but the role of WNT signaling in thymic tumors is largely unknown. Materials & Methods: Expression and function of WNT4 and FZD6 were analyzed using qRT-PCR, western blot, ELISA, in biopsies of non-neoplastic thymi (NT), thymoma and thymic carcinomas (TC). ShRNA techniques and functional assays were used in primary thymic epithelial cells (pTECs) and TC cell line 1889c. Cells were conventionally (2D) grown and in three-dimensional (3D) spheroids. Results: In biopsies, WHO classified B3 thymomas and TCs showed increased WNT4 expression compared to NTs. During short-term 2D culture, WNT4 expression and secretion declined in neoplastic pTECs, but not in 3D spheroids or medium supplemented with recombinant WNT4 cultures. Under the latter condition, growth of pTECs was accompanied by increased expression of non-canonical targets RAC1 and JNK. Down-regulation of WNT4 by shRNA induced cell death in pTECs derived from B3 thymomas and led to decreased RAC1, but not JNK protein phosphorylation. Pharmacological inhibition of NFκB decreased both RAC1 and JNK phosphorylation in neoplastic pTECs. Conclusions: Lack of the age-related decline of non-canonical WNT4 expression in TETs and restoration of declining WNT4 expression through exogeneous WNT4 or 3D culture of pTECs, hints at an oncogenic role of WNT4 in thymic tumors and is compatible with a WNT4 autocrine loop model. Crosstalk between WNT4 and NFκB signaling may present a promising target for combined interventions in TETs.